Prevalence and factors associated with potentially inappropriate medications in elderly stroke patients: A comparison of Beers 2019 and 2023 criteria - Xiaofang Tan; Xiaoqun Lv; Weigen Xiong; Yujuan Liu; Ning Zhang (Saudi Pharmaceutical Journal)
Abstract Background Polypharmacy is widespread among older adults with ischemic stroke (IS), which may increase the prevalence of potentially inappropriate medications (PIMs). This study aimed to determine the prevalence and factors associated with PIMs in hospitalized IS patients using the 2019 and 2023 Beers criteria. Method We conducted a cross-sectional study by extracting electronic medical records of hospitalized elderly IS patients (aged ≥ 65 years) at Jinshan Hospital of Fudan University from January to December 2021. PIMs were identified based on the 2019 and 2023 Beers criteria. The coherence of the two criteria was evaluated via the kappa test. Poisson regression was performed to identify factors associated with PIM use. Results A total of 559 elderly IS patients were included in the study. According to the 2023 Beers criteria, 43.29% of patients used at least one PIM, compared with 38.82% based on the 2019 Beers criteria. The three most frequently identified PIM classes in both versions were antipsychotics, diuretics, and antidepressants. The kappa value was 0.908 (P < 0.001), indicating strong coherence between the two criteria. Female sex, a higher number of prescribed medications, and longer hospital stays were significantly associated with increased PIM use. Across both sets of criteria, the number of prescribed medications was identified as the strongest factor associated with PIM use. Conclusion The overall prevalence of PIMs was slightly higher according to the 2023 Beers criteria than the 2019 version. PIM use was more prevalent among older female IS inpatients with excessive polypharmacy and hospital stays of 21 days or longer.